Adsorption behavior of Congo red dye from aqueous solutions onto exfoliated graphite as an adsorbent: Kinetic and isotherm studies - Pham, Thinh Van; Tran, Thuan Van; Nguyen, Trinh Duy; Tham, Nguyen Thi Hong; Quang, Phan Thanh Tri; Uyen, Dao Thi To U; Le, Nhan Thi Hong; Vo, Dai-Viet N.; Thanh, Nguyen Trung; Bach, Long Giang (Elsevier Ltd, 2019)
Herein, we reported a facile method to fabricate the exfoliated graphite (EG) by Hummer’s method via a two-step procedure including intercalation with a mixture of oxidants (H2O2 and H2SO4), and exfoliation using a microwave system. For the adsorption experiments, effect of contact time (0–210 min), initial concentration (20–60 mg/L), pH (4–10), and EG dosage (0.3– 0.7 g/L) were systematically studied. Moreover, the adsorption kinetics (pseudo-first-order, pseudo-second-order, Elovich, and Bangham) and isotherms (Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich) were carried out to elucidate the mechanism of CR adsorption over EG. Due to high porosity (40.95 m2 /g) and large maximum adsorption capacity of CR (80.775 mg/g), the EG derived from natural graphite can be an effective adsorbent for CR dye treatment in aqueous solution.